Barriers to Micro Food Enterprise Engagement in Business Support Programmes. (August 2014) - Quinn, Barry; McKitterick, Lynsey; McAdam, Rodney; Dunn, Adele
Micro food producers contribute to the fabric of the local rural community and economy in developing a local food culture, employment and gross domestic product (GDP). This paper explores the range and effectiveness of government-based business policies and support programmes at both regional and firm levels for micro food enterprises, and the barriers to micro-firm engagement in such programmes. The authors present empirical evidence from interviews with key stakeholders and micro-sized food producers based in Northern Ireland. The evidence suggests that micro food producers are engaging with introductory levels of support, but that key barriers to further adoption of support include the understanding and coherence of support; regulations and the level of bureaucracy; and various issues concerning networking capabilities. The authors propose areas for future research and highlight the implications for future policy support provision.